SWAT HYDROLOGICAL MODEL OF ZAMFARA WATERSHED OF SOKOTO-RIMA RIVER CATCHMENT, NORTH WEST NIGERIA (Nigerian Journal of Technology, 2025)
This study employs the Soil and Water Assessment Tool (SWAT) hydrological model to comprehensively analyze the water dynamics within the Zamfara watershed. The model's efficacy in assessing diverse hydrological processes is established through meticulous calibration and validation processes. A sensitivity analysis scrutinizes the model's responsiveness to various thresholds in sub-basin delineation and the definition of Hydrologic Response Units (HRUs). The study's outcomes reveal discernible patterns in annual precipitation, groundwater recharge, and evapotranspiration within the basin. These findings shed light on crucial factors that influence the basin's water balance. They underscore the vital necessity of a thorough hydrological understanding to effectively manage water resources in the Zamfara watershed. The assessment of the catchment's hydrology indicates an average annual precipitation of 876.61 mm. Groundwater recharge accounts for 25.07% of the total groundwater system input, averaging 219.77 mm annually. Notably, only 5% of the overall groundwater recharge contributes to replenishing deep groundwater recharge storage, while the remaining portion refills the shallow aquifer. Consequently, evapotranspiration emerges as the most substantial constituent of the water balance, representing 57% with an average of 500.79 mm per year. Runoff constitutes a mere 12.44% of the total basin output, while the remaining components of precipitation are lost. It is essential to highlight that evapotranspiration serves as the primary mechanism for water loss from the catchment. The calibration and validation phase exhibited by the SWAT model within the confines of the study area showcased exceptional efficacy, achieving notably high R-squared (R2) values surpassing the threshold of 0.80 for the designated gauging sites. This remarkable achievement underscores the SWAT model's commendable aptitude and reliability in conducting precise hydrological assessments within the intricate dynamics of the Zamfara watershed. The total groundwater reserve of the watershed catchment area is estimated at 24,767,082 m3. This suggests high amount of groundwater reserve within the study area for both agricultural and domestic usage.